2016
DOI: 10.12968/bjon.2016.25.15.840
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of deep tissue injury: a literature review

Abstract: Deep tissue injury affects patients of all ages in a variety of healthcare settings. It is therefore essential that nurses are aware of the underlying pathogenesis, in order to accurately assess the pressure ulcer risk of vulnerable patients, and to subsequently reduce patient harm. The majority of pressure ulcers are avoidable, however, a variety of intrinsic and extrinsic factors can contribute towards the development of deep tissue injury. Understanding the body's internal responses to external pressure wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…3). Previous research has shown that ischemia-reperfusion injury can promote and aggravate deep tissue injuries and even result in limb gangrene or shedding [5,31], suggesting that tissue hypoxia may play a prominent role in driving the complications associated with deep tissue injuries. Anti-inflammation and angiogenesis mechanisms were shown to be important factors in limiting damage to deep tissue muscle injuries [32,33]; thus, targeting these fundamental mechanisms of wound healing may help to limit damage resulting from pressure wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Previous research has shown that ischemia-reperfusion injury can promote and aggravate deep tissue injuries and even result in limb gangrene or shedding [5,31], suggesting that tissue hypoxia may play a prominent role in driving the complications associated with deep tissue injuries. Anti-inflammation and angiogenesis mechanisms were shown to be important factors in limiting damage to deep tissue muscle injuries [32,33]; thus, targeting these fundamental mechanisms of wound healing may help to limit damage resulting from pressure wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory responses and reductions in capillary density caused by ischemia/reperfusion are the main factors that affect deep tissue injury healing [4,5]. The main principles of deep tissue injury management are in the inhibition of inflammatory responses in conjunction with the restoration of blood microcirculation within the wound site [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…(4) Dado su carácter a menudo crónico, las LPPH tienen un impacto significativo en la evolución y la calidad de vida de los pacientes, incluyendo dolor, depresión y hospitalizaciones prolongadas, lo que aumenta la carga de trabajo para los equipos de salud. (5) Esta situación se torna aún más crítica si se estima que un 95 % de las LPPH son evitables. (6) Varios son los factores que se conjugan en la aparición de LPPH, incluyendo la falta de entrenamiento formal de los trabajadores de salud en su prevención; la inexperiencia en su manejo, (7) elevada carga de trabajo y frecuente rotación de los equipos de enfermería.…”
Section: Introductionunclassified
“…Pressure injury is defined as local skin and subcutaneous soft tissue injury due to shear or friction alone or in combination, usually occurring at the site of bone protrusion in patients immobilized for an extended period ( 8 ). The pathogenesis of pressure injuries is generally recognized to result from tissue ischemia, ischemia–reperfusion injury, and skin injury caused by mechanical load ( 9 , 10 ). The prevalence of pressure injuries among patients in the wards ranged from 4.7 to 32.1%, with a higher incidence of pressure injuries in ICU ( 11 ).…”
Section: Introductionmentioning
confidence: 99%